2021
DOI: 10.3389/fpls.2021.746180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperature on Rice Grain Development and Quality Formation Based on Proteomics Comparative Analysis Under Field Warming

Abstract: With the intensification of global warming, rice production is facing new challenges. Field evidence indicates that elevated temperature during rice grain-filling leads to the further deterioration of grain quality. In order to clarify the potential regulatory mechanism of elevated temperature on the formation of rice quality, the DIA mass spectrometry method under the background of field warming was conducted to investigate the regulatory effects of high temperature on grain development and material accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…During grain development, an increment in temperature of 1.6°C-3.1°C can disturb the accumulation of storage materials (Liu et al, 2021). Previous studies showed that HT can increase protein content (Lin et al, 2010) and was unfavorable for lipid accumulation during rice grain ripening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During grain development, an increment in temperature of 1.6°C-3.1°C can disturb the accumulation of storage materials (Liu et al, 2021). Previous studies showed that HT can increase protein content (Lin et al, 2010) and was unfavorable for lipid accumulation during rice grain ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in AAC under HT may also be dependent on rice varieties. Cheng et al (2005) found that HT increased the AC in high-AC varieties, while Liu et al (2021) found that AC decreased under elevated temperatures. The different responses of AAC in R7954 and mutants RS111 and RS4 to HT (Table 1) might be because of the increased sensitivity of amyloplast enzymes in RS111 and RS4 exposed to HT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heat injury caused by climate warming is a major contributor to the decreases in rice yield and quality (Liu et al, 2021). If the temperature during the vegetative growth period of rice exceeds 35°C, tiller production decreases, the rate of growth in plant height declines, the growth of aboveground and underground plant parts is reduced, and the overall rice development period is shortened.…”
Section: Introductionmentioning
confidence: 99%